Accumulation of and Response to Auxins in Roots and Nodules of the Actinorhizal Plant Datisca glomerata Compared to the Model Legume Medicago truncatula - Demina, Irina V.; Maity, Pooja Jha; Nagchowdhury, Anurupa; Ng, Jason L. P.; van der Graaff, Eric; Demchenko, Kirill N.; Roitsch, Thomas; Mathesius, Ulrike; Pawlowski, Katharina (Frontiers in Plant Science, 2019)
Actinorhizal nodules are structurally different from legume nodules and show a greater similarity to lateral roots. Because of the important role of auxins in lateral root and nodule formation, auxin profiles were examined in roots and nodules of the actinorhizal species Datisca glomerata and the model legume Medicago truncatula. The auxin response in roots and nodules of both species was analyzed in transgenic root systems expressing a beta-glucuronidase gene under control of the synthetic auxin-responsive promoter DR5. The effects of two different auxin on root development were compared for both species. The auxin present in nodules at the highest levels was phenylacetic acid (PAA). No differences were found between the concentrations of active auxins of roots vs. nodules, while levels of the auxin conjugate indole-3-acetic acid-alanine were increased in nodules compared to roots of both species. Because auxins typically act in concert with cytokinins, cytokinins were also quantified. Concentrations of cis-zeatin and some glycosylated cytokinins were dramatically increased in nodules compared to roots of D. glomerata, but not of M. truncatula. The ratio of active auxins to cytokinins remained similar in nodules compared to roots in both species. The auxin response, as shown by the activation of the DR5 promoter, seemed significantly reduced in nodules compared to roots of both species, suggesting the accumulation of auxins in cell types that do not express the signal transduction pathway leading to DR5 activation. Effects on root development were analyzed for the synthetic auxin naphthaleneacetic acid (NAA) and PAA, the dominant auxin in nodules. Both auxins had similar effects, except that the sensitivity of roots to PAA was lower than to NAA. However, while the effects of both auxins on primary root growth were similar for both species, effects on root branching were different: both auxins had the classical positive effect on root branching in M. truncatula, but a negative effect in D. glomerata. Such a negative effect of exogenous auxin on root branching has previously been found for a cucurbit that forms lateral root primordia in the meristem of the parental root; however, root branching in D. glomerata does not follow that pattern.